Bionic hierarchical porous aluminum nitride ceramic composite phase change material with excellent heat transfer and storage performance. (October 2021) - Qiu, Lin; Yan, Kening; Feng, Yanhui; Liu, Xianglei; Zhang, Xinxin
Abstract: In this paper, we synthesized bionic bone hierarchical porous AlN ceramics which encapsulate polyethylene glycol2000 (PEG2000) to form a new composite phase change material. Argon adsorption and SEM demonstrate that the AlN ceramic has hierarchical structure with most probable diameters of 2.4 nm and 27.3 nm. Raman spectroscopy show that no aluminum vacancies are formed inside the material, which effectively reduce the probability of phonon scattering and improve the thermal performance. EDS and XRD demonstrate that the main crystalline phase of the ceramics is AlN with a small amount of impurity peaks. The thermal conductivity of AlN ceramics with a porosity of 75.2% and 67.5% are 5.10 and 13.86 W/m·K, and that of the composite material is 17.16 W/m·K. The latent heat of melting of the composite material is 88.73 J/g and the melting point is 54.75 °C. The material breaks through the defects of slow dynamic response time and low thermal conductivity of traditional energy storage materials. Highlights: ● Relation between thermal transport and hierarchical-pore-structure of AlN is built ● Unique cell-window skeleton structure promotes phase change material to flow ● Anti-hydration treatment can effectively improve the thermal conductivity of AlN ● Thermal contact resistance between AlN skeleton and PEG core material is measured